Educational policies and activities for preschool children: Reflections from the cultural-historical approach and activity theory (2014)
Educational activities employed with preschool children have significance in their development and preparation for school learning. For this reason, it is necessary to analyze the relationship established between educational policies and educational activities for the preschool population in the Colombian context. In this paper, these two aspects interact to contribute to its conclusion. The teacher’s task is to promote the integral development of children and ensure an optimal level of preparation for schooling. Considering current pedagogical practice, this task is not successfully carried out as required by the objectives of educational policy. However, monitoring this psychological and pedagogical approach based on cultural-historical theory highlights both theoretical foundations and methodological pathways for innovating with regard to the educational status of preschool.